Analisis User Experience Pada(s2ti.ftki.unas.ac.id ) S2 Teknologi Informasi Universitas Nasional dengan Menggunakan Metode User Centered Design dan System Usability Scale - Latif Arif Anggoro; Agung Triayudi; Dhieka Avrilia Lantana (STMIK Budi Darma, 2023)
In this era, the use of technology is becoming a new habit, in searching for information, technological developments are also not spared because technology can shorten time. When searching for information on website pages, users not only see the contents of the news presented but users also see whether the appearance on the website is attractive or not. Because by using an attractive appearance, users will increase their sense of exploration when operating the website. In this research, researchers will examine the user experience of users when using the Information Technology Masters website which will later be developed into a user interface and user experience design. At the stage of conducting an analysis to determine the requirements to be used, the researcher uses the User Centered Design method, and in this design gets 4 user roles, namely ordinary users, students, lecturers, and admins. In addition, researchers conducted an analysis of website usability to measure user satisfaction using the System Usability Scale method. This test involved 35 respondents who would carry out usability testing on the questionnaire, then the data was processed using the SUS method and the SUS score was 77.3 with this score. the implementation of the ui/ux design makes it easy for users and gets grade B+ on the guideline for calculating the SUS method score